A new species of Simpsonichthys (Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, northeastern Brazil - Nielsen, Dalton Tavares Bressane; Shibatta, Oscar Akio; Suzart, Rogério Dos Reis; Martín, Amer Faour (Zootaxa, 2010)
Simpsonichtys lopesi n. sp. is described from a temporary pool located in the São Francisco river basin. This species is distinguished from remaining species, except S. adornatus, by the large number of dorsal fin rays, which makes possible a large dorsal fin base length that begins well anterior to the middle of the body, before the vertical line through the pelvic fin. This species differs from S. adornatus by the color pattern of the anal fin, which may have yellow stripes or light dots (vs. small light points), and also by the lower number of dorsal fin rays.